National Survey of Pharmacy Leadership at Ministry of Health in Saudi Arabia: Problem-solving and Decision-making - Alomi, Yousef Ahmed; Abdulmohsen Albaz, Modhi; AlMuhraj, Wejdan Fawzan; AlKharji, Mashael Yasser; Alshuraym, Norah Rushud (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the national survey of pharmacy leadership at the Ministry of Health with emphasis on pharmacy Problem solving and decision making. Methods: It is a ninety days cross-sectional national survey of pharmacy leadership practice at Ministry of Health. The survey modified from self-assessment of 360 leadership and with pharmacy leadership literature. It consisted of a demographic section, leadership pathway, and fifty-three leadership questions. It contained selected eighteen leadership skills of 360 leadership self-assessment. The leadership skills included Achievement, Goals, Flexibility, Feedback, Excellence, Empowering Others, Emotional Intelligence, Decision Making, Developing Others, Cultural Awareness, Continual Improvement, Communication Skills, Coworker Development, Leading the Change Needed, Attitude, Analytical, Administrative Skill, and Action. The electronic format of the survey through survey monkey system and distributed through emails. A reminder e-mail containing a link to the website forwarded two weeks after. All analysis is done through survey monkey system. The survey divided into for several parts for analysis, and discussion. Part one: practice management, part two: planning and organizations, part three: communications strategies, part four: problem-solving and decision making, part five: performances management, part six; working environment, and part seven: professional development. The study explored the part number four; National Survey of Pharmacy leadership: Problem-solving and decision-making. Results: The survey distributed to one hundred hospitals, the response rate, was forty-two hospitals (42%) with seventy-pharmacy leaders. The gender distribution of responders was Male 43 (63.24%) and female 25 (36.76%) while the nationality was Saudi 69 (98.57%) and non-Saudi one (1.43%). The majority of responders were in age range (25-34) years 30 (55.12%) and (35-44 years) 26 (38.24%). The average score decisionmaking skills were 2.53 (84.32%) with the highest score was Uses data from different sources to confirm information 2.7 (89.99%), and the lowest score was Make sound and timely decisions under pressure 2.25 (74.99 %). While average score Feedback skills were 2.6 (86.99 %) with the highest score was open to the suggestions of others 2.71 (91.32%), and the lowest score looked to others for input 2.46 (81.99%). The Emotional Intelligence skills average score was 2.63 (87.65%) with the highest score was Helps employees to resolve conflicts, communicate clearly, and work together to solve problems 2.69 (89.65%) and lowest score can express themselves 2.45 (81.65%). Conclusion: The problem solving and decision making of Pharmacy leaders in acceptable at Ministry of Health organization. Targeting of improving the particle skills through established the Advance training in the pharmacy management is necessary at Ministry of Health institutions in the Kingdom of Saudi Arabia.
Keywords: Pharmacy leadership; Problem-solving; Decision making; Ministry of health; Saudi arabia